Fluctuation effects in initial conditions for hydrodynamics - Paiva, Samya [UNESP]; Hama, Yogiro; Kodama, Takeshi (American Physical Society (APS), 1997)
We have studied the fluctuation effects in proton-proton collisions through the analysis of their observables. To investigate the role of fluctuation 5 in the initial conditions, we have used the interacting gluon model, modified by the inclusion of the impact parameter, and have applied the one-dimensional Landau's Hydrodynamical Model to the fireballs thus generated. The rapidity and pseudorapidity distributions were calculated using two distinct procedures, one taking the fluctuations into account and the other the usual method considering only one fireball with the average initial conditions. The results show indeed the importance of fluctuations.